Adaptive Physical Education Learning in Special Need Schools during the Pandemic - Utama, Dimas Duta Putra; Putri, Alifia Ramadhina (TEGAR: Journal of Teaching Physical Education in Elementary School, 2021)
Adaptive Physical Education learning during the pandemic, in general, still has several problems requiring a solution. One of the most important issues is that the teaching material used by teachers no longer meets the pandemic conditions. Children with special needs cannot learn according to the rules that have been carried out before. Some of the obstacles occurred in the field are caused by the existed learning facilities and infrastructure that do not support teachers in conducting Physical Education learning. Therefore, the research was carried out to explain the implementation of Adaptive Physical Education learning in Special Need Schools in the current pandemic. This research used quantitative descriptive with survey method to gain the latest data about Physical Education learning. The data were directly taken from 20 Special Need School teachers in Bandar Lampung City. The finding concluded that the implementation of Adaptive Physical Education learning in Special Need Schools in Bandar Lampung was in the good category, reaching a percentage of 40%. However, it is important for the teachers to create new innovations to provide more interesting learning for students with special needs in Special Need Schools.Â